2018
DOI: 10.1002/aqc.2985
|View full text |Cite
|
Sign up to set email alerts
|

How to coexist with the ‘killer shrimp’ Dikerogammarus villosus? Lessons from other invasive Ponto‐Caspian peracarids

Abstract: Studying interactions among co‐evolved invaders might help us in understanding, predicting, and perhaps mitigating the impact of the invading species on the native biota. The factors of spatial niche differentiation were investigated among invasive Ponto‐Caspian peracarids with the aim of revealing how co‐evolved species can coexist with the ‘killer shrimp’ Dikerogammarus villosus, an invasive gammarid replacing non‐Ponto‐Caspian species throughout Europe. Multi‐habitat samples from the third Joint Danube Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Already in the 1950s, the demon shrimp was reported from the middle Danube above Györ in Hungary, and in 1994, it was found as high as the Danube-Main canal in Germany (Straškraba 1962;Schleuter et al 1994;Borza et al 2015). In the early 1990s it was abundant in the German part of the Danube, but soon after the appearance of the killer shrimp, the population of demon shrimp in that area declined (Weinzierl et al 1996;Kley and Maier 2006;Borza et al 2018). Similar observations were made in other rivers: Rhine, Lahn, Drava, Oder, and Vistula (Weinzierl et al 1996;Bernauer and Jansen 2006;Kley and Maier 2006;Grabowski et al 2007b;Chen et al 2012;Ćuk et al 2019; own unpublished data), suggesting effective replacement of this species by D. villosus, even if in some conditions co-existence of D. haemobaphes and D. villosus was observed (Borza et al 2017;Hellmann et al 2017).…”
Section: Invasion Routesmentioning
confidence: 99%
“…Already in the 1950s, the demon shrimp was reported from the middle Danube above Györ in Hungary, and in 1994, it was found as high as the Danube-Main canal in Germany (Straškraba 1962;Schleuter et al 1994;Borza et al 2015). In the early 1990s it was abundant in the German part of the Danube, but soon after the appearance of the killer shrimp, the population of demon shrimp in that area declined (Weinzierl et al 1996;Kley and Maier 2006;Borza et al 2018). Similar observations were made in other rivers: Rhine, Lahn, Drava, Oder, and Vistula (Weinzierl et al 1996;Bernauer and Jansen 2006;Kley and Maier 2006;Grabowski et al 2007b;Chen et al 2012;Ćuk et al 2019; own unpublished data), suggesting effective replacement of this species by D. villosus, even if in some conditions co-existence of D. haemobaphes and D. villosus was observed (Borza et al 2017;Hellmann et al 2017).…”
Section: Invasion Routesmentioning
confidence: 99%
“…In the wild, D. haemobaphes can retreat to habitats avoided by its stronger competitor, e.g. with stronger water flow (Borza et al 2018). Anyway, our study shows that, when migration is not possible, D. haemobaphes is capable of withstanding the direct co-existence with D. villosus without any visible negative consequences in shelter use, at least over a short term tested in our study.…”
Section: Interspecific Interactions Among Amphipodsmentioning
confidence: 49%
“…An affinity for hard substrata has been proposed as an important factor favoring the dispersal of Ponto-Caspian peracarid crustaceans into heavily anthropized habitats (Borza et al 2017). Indeed, numerous studies reported a preference of alien Ponto-Caspian amphipods for hard substrates, although relatively few species were studied thus far (Dermott et al 1998; Hesselschwerdt et al 2008; Jermacz et al 2015; Borza et al 2018; Poznańska-Kakareko et al 2021). Clingers and symbionts seem to be associated with more specific substrates, which may limit dispersal potential.…”
Section: Discussionmentioning
confidence: 99%